Properties and potentialities of hyaluronic acid and eXcellent Tridimensional Reticulation as a filling agent: a review - Vincent Wong; Martina Manni (Drugs in Context)
Cutaneous ageing has attracted widespread interest in recent decades, and the global market for non-invasive rejuvenation procedures is expanding, with hyaluronic acid (HA)-based fillers playing a significant role. The conversion of HA into a filler product is a complex and multidimensional process that involves several key stages. Each HA-based filler has rheological features that vary depending on the manufacturing process and lead to particular behaviours when injected into specific anatomical locations. Clinicians must be equipped to select dermal fillers with properties that align with the intended aesthetic outcome. Several key factors influence this decision, including the anatomical characteristics of the injection site, the consistency and thickness of the surrounding tissues, the firmness of retaining structures, the degree of mimetic muscle activity and external mechanical forces on the face as well as the specific anatomical plane targeted for injection. These variables differ not only by facial region but also between individuals, highlighting the importance of thorough patient evaluation. HA fillers are widely recognized for their safety and biocompatibility, with most adverse effects being localized and transient, typically occurring at or near the injection site. Our literature review covers the capabilities and potentials of HA and eXcellent Tridimensional Reticulation (XTR™) in the treatment of skin ageing.